Correlation between Care Burden and Mental Health with the Perceived Social Support of Patients Relatives in Turkey - TAHTA, Mehtap ŞAHİNGÖZ; BALCI, Elçin (Kesmas, 2021)
The people providing care for relatives always need support and accompaniment from their families and friends. This study aimed to evaluate the correlation among the care burden, mental health and social support perceptions of the patients’ relatives that provide long-term care for patients receiving service from the home care service (HCS) unit in one city. This descriptive study was carried out with the relatives of patients receiving service from home health units. Among the relatives providing care for a total of 859 patients, those that did not comply with the inclusion criteria were excluded, which made a total population of 309 people. Individual information form, burden interview, brief symptom inventory and multidimensional scale of perceived social support were used for the assessment of the data. Descriptive statistics and Spearman’s correlation coefficient were used for data analysis. The result showed a positive moderate significant correlation among the burden score, brief symptom inventory subscale and global index scores while, a negative moderate significant correlation was discovered between the family, significant other and multidimensional scale of perceived social support scores. Consequently, as the perceived social support level in the patients’ relatives providing care increased, their care burden and mental health problems decreased.